Automatic identification of terpenoid skeletons by feed-forward neural networks - Emerenciano, Vicente P.; Alvarenga, Sandra A. V.; Scotti, Marcus Tullius; Ferreira, Marcelo J. P.; Stefani, Ricardo; Nuzillard, Jean-Marc (Elsevier B.V., 2006)
Feed-forward neural networks (FFNNs) were used to predict the skeletal type of molecules belonging to six classes of terpenoids. A database that contains the (13)C NMR spectra of about 5000 compounds was used to train the FFNNs. An efficient representation of the spectra was designed and the constitution of the best FFNN input vector format resorted from an heuristic approach. The latter was derived from general considerations on terpenoid structures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: artificial neural networks; (13)C NMR; spectroscopy; terpenoids; steroids